2023
DOI: 10.1093/europace/euad224
|View full text |Cite
|
Sign up to set email alerts
|

REducing INFectiOns thRough Cardiac device Envelope: insight from real world data. The REINFORCE project

Abstract: Background Infections resulting from cardiac implantable electronic device (CIED) implantation are severely impacting on patients’ and on health care systems. The use of TYRXTM absorbable antibiotic-eluting envelope has proven to decrease major CIED infections within 12 months of CIED surgery. Aims to evaluate the impact of the envelope use on infection-related clinical events in a real-world contemporary patient population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The benefit of AEE was sustained during long-term follow-up [83]. A meta-analysis summarizing a major observational and randomized trials and a recent real-world study demonstrated similar findings [84,85]. Further analyses of the WRAP-IT population showed a more than 11-fold higher risk of major CIED infection in patients with pocket hematoma and without the AEE [34].…”
Section: Antibiotic Eluting Envelopesmentioning
confidence: 78%
“…The benefit of AEE was sustained during long-term follow-up [83]. A meta-analysis summarizing a major observational and randomized trials and a recent real-world study demonstrated similar findings [84,85]. Further analyses of the WRAP-IT population showed a more than 11-fold higher risk of major CIED infection in patients with pocket hematoma and without the AEE [34].…”
Section: Antibiotic Eluting Envelopesmentioning
confidence: 78%
“… 36 The efficacy of the envelope has since been corroborated in other settings. 37–39 The use of the antibacterial envelope in the WRAP-IT population and in high-risk subgroups and procedures was recommended in the 2019 European Heart Rhythm Association (EHRA) International Consensus document and in the 2021 ESC Pacing Guidelines in Pacemaker re-interventions (Class IIb). 18 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…This benefit was reproduced in subsequent studies, such as the REINFORCE project which analyzed the outcomes of 1819 patients undergoing CIED procedures (872 with AE, 947 without), and demonstrated significantly lower infection event rates in the AE group (0.8% vs . 2.4%, respectively; p = 0.007) [ 70 ]. Furthermore, a meta-analysis conducted by Asbeutah et al .…”
Section: Methods To Prevent Cied Infectionsmentioning
confidence: 99%